The passage of literature genealogies of modernism in Conrad, Rhys, and Pramoedya - GoGwilt, Christopher Lloyd (Oxford University Press, 2011)
Reevaluating 20th century literature and culture, this book studies the interrelations between English, Creole, and Indonesian formations of literary modernism. Each modernist formation is explained through a set of comparative studies of the fiction of Joseph Conrad, Jean Rhys, and Pramoedya Ananta Toer.